2009
DOI: 10.1590/s1677-55382009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on ureteroscopic laser lithotripsy of urinary tract calculi

Abstract: Purpose: The treatment of urinary tract stones in obese patients may differ from the treatment of non-obese patients and their success rate varies. Our objective was to compare ureteroscopic treatment outcomes of ureteral and renal stones, stratified for stone size and location, between overweight, obese and non-obese patients. Materials and Methods: Charts were reviewed for 500 consecutive patients presenting at our institution for renal and ureteral stones. A total of 107 patients underwent flexible or semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Results from a retrospective, single-institution study showed that the stone-free rates among 107 obese and non-obese patients were similar. [22] Another study by Best et al [23] also showed similar success rates. However, these studies provided only limited information regarding intra-and postsurgical anesthesia-related complication rates in obese patients.…”
Section: Discussionmentioning
confidence: 76%
“…Results from a retrospective, single-institution study showed that the stone-free rates among 107 obese and non-obese patients were similar. [22] Another study by Best et al [23] also showed similar success rates. However, these studies provided only limited information regarding intra-and postsurgical anesthesia-related complication rates in obese patients.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, ureteroscopy does not appear to be affected by body habitus. In a retrospective, single institution study, the stone free rates were similar between 107 obese patients and non-obese patients (21). Another recent study published by Best et al (22) showed statistically equivalent SFR in obese (91%) and non-obese (81%) patients who underwent flexible URS for proximal ureteral stones.…”
Section: Discussionmentioning
confidence: 82%
“…Extracorporeal shock wave lithotripsy may be a suboptimal treatment for obese patients since positioning of the patient for an optimal stone fragmentation is a limiting factor [7] . Most lithotripters have a maximum skin to stone distance of 12-14 cm for their focal point and thus can restrict the acquired distance for complete stone fragmentation in obese patients [7,27] .…”
Section: Management Of Obese Patients With Urolithiasismentioning
confidence: 99%
“…Most lithotripters have a maximum skin to stone distance of 12-14 cm for their focal point and thus can restrict the acquired distance for complete stone fragmentation in obese patients [7,27] . Similar difficulties may also decrease the success rate of a percutaneous nephrolithotomy (PCNL) procedure in an obese patient with nephrolithiasis due to difficulties in percutaneous access, as well as limitations in the use of normal sized instruments and higher risk of anesthetic complications in prone position [7] . In contrast, El-Assmy et al [28] showed that PCNL in obese patients is a safe method with similar success rates, morbidity and operative time.…”
Section: Management Of Obese Patients With Urolithiasismentioning
confidence: 99%
See 1 more Smart Citation